2003
DOI: 10.1007/s00425-002-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of salt stress-enhanced phosphoenolpyruvate carboxylase kinase activity in leaves of Sorghum vulgare: independence from osmotic stress, involvement of ion toxicity and significance of dark phosphorylation

Abstract: C 4 phosphoenolpyruvate carboxylase (PEP-Case: EC 4.1.1.31) is subjected to in vivo regulatory phosphorylation by a light up-regulated, calciumindependent protein kinase. Salt stress greatly enhanced phosphoenolpyruvate carboxylase-kinase (PEPCase-k) activity in leaves of Sorghum. The increase in PEPCase-k anticipated the time course of proline accumulation thereby suggesting that water stress was not involved in the kinase response to salt. Moreover, osmotic stress seemed not to be the main factor implicated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 48 publications
7
35
0
1
Order By: Relevance
“…The only protein that was up-regulated upon mannitol treatment was PEPC. This is in agreement with previous studies where it was shown that abiotic stresses can induce PEPC gene expression in wheat, A. thaliana , and sorghum (Echevarría et al , 2001; González et al , 2003; García-Mauriño et al , 2003; Sánchez et al , 2006). Moreover, recent studies demonstrated that the maize PEPC gene was able to confer drought tolerance and increase grain yield in transgenic wheat plants (Qin et al , 2016).…”
Section: Discussionsupporting
confidence: 94%
“…The only protein that was up-regulated upon mannitol treatment was PEPC. This is in agreement with previous studies where it was shown that abiotic stresses can induce PEPC gene expression in wheat, A. thaliana , and sorghum (Echevarría et al , 2001; González et al , 2003; García-Mauriño et al , 2003; Sánchez et al , 2006). Moreover, recent studies demonstrated that the maize PEPC gene was able to confer drought tolerance and increase grain yield in transgenic wheat plants (Qin et al , 2016).…”
Section: Discussionsupporting
confidence: 94%
“…5; Supplementary Table S4). Previous reports also demonstrated the crucial roles of PEPC genes in various stress responses and in hormone signaling transduction278910, which motivated us to perform expression profile analyses of GmPEPC genes under various abiotic stress and hormones treatments. The results showed that Al, cold, salt or PEG stress could alter the expression level of soybean PEPC genes and soybean PEPC activity (Figs 7 and 8).…”
Section: Discussionmentioning
confidence: 97%
“…For example, studies have shown that PEPC overexpressing transgenic rice has a relatively higher photosynthetic rate under high light and temperature conditions53. In addition, abiotic stresses, such as salt and chilling injury, can induce PEPC gene expression in wheat, Arabidopsis and sorghum81054. In this study, we showed that the promoter regions of most GmPEPC genes contained 19 stress-responsive cis -regulated elements such as ABA, cold, drought, heat, salt, and wound-related elements, indicating their potential roles in soybean response to phytohormone and stresses (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PEPC plays roles in fruit ripening, regulating cellular pH, and providing malate to guard cells [69]. PEPC kinase is a Ca 2+ -independent serine/threonine kinase that phosphorylates PEPC; strikingly, PEPC kinase activity was enhanced by salt stress in Sorghum vulgare ; further analysis revealed that the induction was related to ion toxicity rather than osmotic stress [70]. Although it is uncertain which aspect of PEPC function caused its responsiveness to LCO foliar spray, any of the three indicated could be affected.…”
Section: Discussionmentioning
confidence: 99%